(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Palonosetrone is a potent, single stereoisomeric 5-HT3RA, with a structure based on a fused tricyclic ring system attached to a quinuclidine moiety - unique and different from first-generation 5-HT3RA, therefore aim of our study was to find out betterment of palonosetrone as PONV management in comparison to granisetrone. Objectives: The purpose of the present study was to evaluate the effectiveness of Palonosetrone in comparison with Granisetrone in preventing Postoperative nausea and vomiting. Methodology: The patient with ASA grade I, II and age between (20-50) years undergoing surgery under general anaesthesia having no pathology or deformity causing vomiting were selected after their admission in Bangladesh Medical college and hospital from November 2019 to May 2020, Department of Anaesthesiology & ICU, Bangladesh Medical College & Hospital, Dhaka. The selected patients were divided in two groups. Both the group was given a prospective randomized trial were conducted on a total of 60 patients of ASA grade I and II and mallampati I & II of either sex between age group of 20 to 50 years, scheduled for general anaesthesia were selected at random. Results: The overall incidence of PONV was 26.67 % for group A and 63.33% for group B. The number of complete responders to drugs at 24 hr after the surgery was 22 (73.33 %) for palonosetrone and 11 (36.67%) for granisetrone representing statistical difference (P = 0.035). Conclusion: Palonosetrone is more effective in the prevention of PONV in patients undergoing elective surgerys under general anaesthesia as compared to granisetrone, especially in the 2-24 h period postoperatively. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):52-57